Novel Cyclopropylindole Conjugates and Dimers Synthesis and Anti-Cancer Evaluation - Sharma, Sanjay K.; Jia, Guofeng; Lown, J. W. (Current Medicinal Chemistry - Anti-Cancer Agents, 2001)
There is a considerable interest currently in the development of DNA sequence specific or selective agents for genetic targeting for the control of gene expression, for application in diagnosis or ultimately in therapy. In this context CC-1065 is one of the most impressive lead compounds isolated in trace quantities from the culture of Streptomyces zelensis at Upjohn in 1978. The unique structure was confirmed by single X-ray in 1981. However CC-1065 cannot be used in humans because it was found that it caused delayed deaths in experimental animals. In the search for compounds with better antitumor selectivity and DNA sequence specificity many CC-1065 analogs have been synthesized in an attempt to avoid the undesired side effects while retaining its potency against tumor cells. Two successful attempts in the modification in the active moiety of the parent natural product 1,2,8,8a-tetrahydro-7-methylcyclopropa[3,2-e]indole-4- one (CPI) and 1,2,9,9a-tetrahydrocyclopropa[c]benz[e]indole-4-one (CBI) have been made. We review here recent progress with the analogs of CPI and CBI and their conjugates both by solution and solid phase, also the progress and development of CPI and CBI conjugates with polyamides (information reading molecules in the minor groove of DNA). Since CPI-CPI dimers are significantly more potent than CC-1065 in vitro and in vivo, a large number of CBI-CBI dimers with varying linkers lengths and positions synthesized in our group and their pharmacological properties have been reviewed.
Keywords: mitomycin